Enhancing 3R (Reuse, Reduce, Recycle) Awareness through E-Book Design as a Sustainable Waste Management Solution - Galih Indra Permana (Faculty Of Arts and Design Sebelas Maret University, 2026)
This study entitled “Enhancing 3R (Reuse, Reduce, Recycle) Awareness through E-Book Design as a Sustainable Waste Management Solution” focuses on the development of an educational e-book aimed at increasing public awareness of 3R practices in Indonesia, with Surakarta City as one of the case examples. This research is motivated by the low level of public understanding and implementation of sustainable waste management practices in various regions of Indonesia. The purpose of this study is to design an e-book based on visual communication design principles that is visually engaging, easy to understand, and capable of encouraging the application of the 3R (Reuse, Reduce, Recycle) concept in daily life. A qualitative research methodology was employed, including observation, interviews, questionnaires, and literature review. The results indicate that informative, interactive, and visually consistent visual content delivered through e-book media can effectively enhance public understanding and interest in implementing 3R principles. Therefore, the designed e-book is expected to strengthen public awareness at the national level and serve as an effective educational medium to promote sustainable waste management behavior in Indonesia. Keywords: 3R Awareness, E-book Design, Sustainable Waste Management, Visual Communication Design